Exposure to Shampoo Made from Bangle Rhizome Extract (Zingiber montanum) to Histopathological Changes in the Kidney of Mice (Mus musculus) - Rina Priastini Susilowati; Adit Widodo Santoso; Budiman Hartono (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Pyrethroid pesticide poisoning cases in developed and developing countries have a high incidence every year. One of the pyrethroid active substances that is widely used as an ingredient in anti-human lice shampoo (Pediculus humanus capitis) is permethrin 1%. The poisoning effect of permethrin-based shampoo as an anti-lice shampoo has been little studied, and there is a need to find alternative active ingredients from plants as a substitute for 1% permethrin, namely bangle (Zingiber montanum). The purpose of this study was to determine the toxicity of using shampoo made from 1% permethrin and made from bangle rhizome extract with graded doses through changes in kidney histopathology. The type of research was post test only control complete randomized design using 25 male mice, which were randomly divided into 5 groups, namely negative control (baby shampoo), positive control (1% permethrin shampoo), shampoo treatment made from bangle rhizome extract with graded doses (0.5%, 1%, and 2%). The shampoo was applied topically on the head for 14 days. After the mice were sacrificed, the kidneys were processed into tissues by paraffin method and stained with HE. Renal tubular injury was examined using a 400x magnification light microscope. The results showed the average changes in kidney histopathology in mice treated with 1% permethrin shampoo and 2% bangle rhizome extract shampoo, although not significantly different (p>0.05). Histopathological changes in the kidneys of mice that were seen were fatty degeneration which caused swelling of the proximal tubules and necrosis of kidney cells